Radiation exposure in prone vs. modified supine position during PCNL: Results with an anthropomorphic model - St-Laurent, Marie-Pier; Doizi, Steve; Rosec, Maéva; Terrasa, Jean-Baptiste; Villa, Luca; Traxer, Olivier; Cloutier, Jonathan (Canadian Urological Association Journal, 2019)
Introduction: Radiation exposure during urological procedures is still of concern in the urology community. It has been reported that percutaneous nephrolithotomy (PCNL) in supine position has less irradiation, as the puncture is mostly done under ultrasound guidance. However, it can also be done under fluoroscopy guidance. Unfortunately, data on radiation exposure during PCNL is lacking since they are often drawn from generalization and extrapolation, or they do not evaluate new procedures or different positions. The aim of our study was to compare the radiation dose depending on the position of the surgeon during PCNL. Methods: A portable C-arm was used in standard mode (32 impulsions/ second; 98 kV, 3.8 mA). Specific dosimeters were placed for lens, extremity, and torso. Anthropomorphic models and hand phantom models were used to reproduce the position of surgeon and patient (with same bone density as human) during PCNL in prone and modified supine position. Fluoroscopy time (FT) was six minutes to obtain higher exploitable signal, and the results are given for a FT of three minutes (more realistic). Ten percent of the FT is done with an angulation of 15 degrees and the rest in anteroposterior position. Results: The equivalent doses (ED) are given in uSV (uncertainty k=2). During the modified supine position: neck, lens, right index finger, left thumb, and index finger received EDs of 99 (20%), 62 (18%), 437 (10%), 112 (12%), and 204 (10%), respectively. In a prone position, the phantom received ED on the neck, lens, right thumb and index finger, left thumb and index finger of 85 (20%), 92 (12%), 401 (10%), 585 (10%), 295 (10%), and 567 (10%), respectively. In both positions, the right hand seems more exposed than the left hand. Conclusions: The effective dose is 1.5- and 1.3-fold higher for lens and extremities, respectively, in prone position PCNL compared to modified supine position. Both positions are still well below the recommended limit for professional exposure